SCIENTIFIC ACTIVITY OF ACADEMICIAN B. ORUZBAEVA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article talks about the scientific activities of Academician B. Oruzbaeva. It is mentioned that Oruzbaeva graduated from the M. Gorky Pedagogical School in Karakol, the Pedagogical Institute, the Faculty of Kyrgyz Language and Literature of the Kyrgyz State Pedagogical Institute in Frunze, and graduate school at the Kyrgyz Branch of the USSR Academy of Sciences. The article notes that B. Oruzbaeva’s scientific activity begins at the Institute of Language and Literature of the Academy of Sciences of the Kyrgyz Academy of Sciences. She worked her way up from the position of researcher to the director of the named institute. It is emphasized that B. Oruzbaeva defended her PhD thesis on the topic “The past tense of the verb in the Kyrgyz language”, as well as her doctoral dissertation on the topic “Word formation in the modern Kyrgyz language”. The article discusses analyzes of the scientific work of B. Oruzbaeva on the topic of the past tense of the verb in the Kyrgyz language, word-formation affixes in the Kyrgyz language, the formation of words in the Kyrgyz language, word, word structure, etc. The great contribution of Academician B. Oruzbaeva to the development of Kyrgyz linguistics is noted.
Keywords: pedagogical institute, Academy of Sciences of the Kyrgyz Republic, candidate’s the sis, doctoral dissertation, past tense of the verb, derivational affixes, word, word structure